Transational Corporations and Regional Production Networks in Asia and the Pacific Region - Jankowiak, Anna (Studia Oeconomica Posnaniensia, 2017)
The Asia Pacific region is characterized by a high degree of investment attractiveness and a competitive location for many global transnational corporations. Production is based on components produced locally as a result of the establishment of strong production networks in the region, the low cost of transport and customs facilitation in the Asia Pacific region, in particular in the group of ASEAN. The cost of production and the transportation of individual components needed, e.g. in the automotive industry or IT is crucial in the decision making process of the unfolding chain of production by a country. Strong economic ties and integration processes taking place on a regional scale are crucial for the region and access to the global market through transnational corporations and production networks is necessary for the further economic development of the region. The aim of the article is to identify models of production networks created by transnational corporations in the Asia Pacific region. Production networks operating in the region and in the ASEAN group of countries, which are becoming an important production center, will be subject to a detailed analysis. This article is based on a descriptive method and the analysis and comparison of secondary sources mainly related to the production networks created by corporations in Asian countries. The analysis covered the available Polish and foreign literature dealing with topics related to the investment attractiveness of the market and the individual countries of the Asia and Pacific region in the context of production network formation. The article attempts to outline the investment attractiveness of the studied region in the context of foreign investment made by corporations operating in production networks, which can be a direct implication for economic practice. The article is a voice in the debate on scientific models of production networks operating in different national economies and regions of the world.